Reading Emerson and Tagore in the Age of Religious Intolerance - Anwaruddin, University of Toronto, Canada, Sardar M. (Asiatic: IIUM Journal of English Language and Literature, 2013)
The greatest problems of the world result from people of different cultures, races and religions being unable to get along and to work together to solve problems such as racism, religious extremism, terrorism and ethnic conflicts. These problems have implicated our contemporary time, especially the post-9/11 era, with anxiety, fear, and suspicion. In this crucial phase of human history, we need what Martha Nussbaum calls an â€œimaginative capacityâ€ to see how the world looks from the point of view of a person who has a different religion. In this article, I discuss the religious thoughts of Ralph Waldo Emerson (1803-82) and Rabindranath Tagore (1861-1941). Although they lived in different cultures and belonged to different literary periods, their intellectual correspondence shows how both of them transcended contemporary religious traditions and established an original relationship with the Supreme Being. It is my hope that this comparative analysis, thus far unexplored, will provide us with insights into understanding religion with an â€œimaginative capacityâ€ at a time when religious intolerance is disrupting peace across the globe.